THE EFFECT OF LEARNING MOTIVATION AND SELF-CONCEPT ON MATHEMATICAL PROBLEMS - Baso Intang Sappaile; Triyanto Pristiwaluyo (Universitas Negeri Makassar, 2019)
This research is a survey research that is focused on the ability of students to solve mathematical problems. The purpose of the study was to determine the relationship between learning motivation and self-concept of students with the ability to solve mathematical problems, both together and individually. The population of the study is 2017/2018 odd semester students of Mathematics Education Study Program FMIPA UNM Makassar. Sampling is used random class. Data obtained through instruments: 1) learning motivation scale, 2) self concept scale, 3) test mathematical problem solving ability. Data were analyzed by multiple regression. The conclusions obtained are 1) learning motivation has a positive relationship with mathematical problem solving abilities, 2) self-concept has a positive relationship with mathematical problem solving abilities, and 3) contribution of motivation and self-concept to mathematical problem solving by 71%. It is expected that other researchers to expand the population and add independent variables that theoretically adhere to mathematical problem solving abilities